2016
DOI: 10.1177/1350507616679347
|View full text |Cite
|
Sign up to set email alerts
|

Globalization routes: The pursuit of conformity and distinctiveness by top business schools in India

Abstract: In this article, we examine how leading business schools in India orient themselves locally and globally while pursuing conformity and distinctiveness. We expect that these dynamics are particularly complex in 'emerging' economies such as India where liberalization and subsequent economic resurgence have led to more intense global exposure for business schools. By exploring changes in the way these responses are applied over time, we identify four globalization routes in the field. Furthermore, we show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 95 publications
(114 reference statements)
0
15
0
Order By: Relevance
“…The effects of business school globalization can be seen in India where institutions are under increasing pressure to become 'world class educational institutions' (Murthy et al, 2007) and produce 'global managers' (Sheth, 1991;Khatri et al, 2012). There has also been significant growth in the number of new business schools (FICC, 2011;Mahajan, Agrawal, Sharma & Nanjia, 2014): in 2005/6 there were 1,888 management institutes, by 2010/11 this had risen to 3,858 (Vakkayil & Chatterjee, 2017). This has generated concerns about the quality of management education in India related to shortages of faculty and the adequacy of educational systems and processes of regulation (Panda & Gupta, 2014;Sheel & Vohra, 2014;Mahajan et al, 2014).…”
Section: Management Education In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of business school globalization can be seen in India where institutions are under increasing pressure to become 'world class educational institutions' (Murthy et al, 2007) and produce 'global managers' (Sheth, 1991;Khatri et al, 2012). There has also been significant growth in the number of new business schools (FICC, 2011;Mahajan, Agrawal, Sharma & Nanjia, 2014): in 2005/6 there were 1,888 management institutes, by 2010/11 this had risen to 3,858 (Vakkayil & Chatterjee, 2017). This has generated concerns about the quality of management education in India related to shortages of faculty and the adequacy of educational systems and processes of regulation (Panda & Gupta, 2014;Sheel & Vohra, 2014;Mahajan et al, 2014).…”
Section: Management Education In Indiamentioning
confidence: 99%
“…In elite institutions there has been an emphasis on producing global research, as schools have sought to enhance their position in international rankings (Banerjee, 2013) by encouraging faculty to publish in journals listed in the Financial Times 'Top 40' (Khatri, Ojha, Budhwar, Srinivasan & Varma, 2012). This has led to greater diversification between institutions, as some schools pursue distinctive accommodation of local orientations while others prioritize conformity to global institutional norms (Vakkayil & Chatterjee, 2017). This context provides the conditions within which Indian management scholars perform their identities, in ways which are, as we argue below, shaped by neo-colonial relations including 'Western othering… and attempts to universalize Western approaches' (Ulus, 2005: 891).…”
Section: Management Education In Indiamentioning
confidence: 99%
“…In this study, participants showed a paradoxical interplay of acceptance-resistance towards fully embodying certain Western beliefs and yet staying true to their original ideals (e.g. Vakkayil and Chatterjee, 2017). By using Bourdieu's notion of position-taking along with a postcolonial lens, in this section, I argue that encouraging critical dialogue with Pakistani MBA students without taking consideration of their social, cultural or historical legacy only reinforces colonial and power relations (e.g.…”
Section: Discussionmentioning
confidence: 79%
“…Although globalization is a multifaceted phenomenon, some studies (e.g. Joy and Poonamallee, 2013; Vakkayil and Chatterjee, 2017) point towards the impact on non-Western business schools which are often prompted to import Westernized practices, including the adoption of rankings, accreditations, pedagogies and partnerships, to become global. This ideology, however, mainly emanating from the West presents a series of challenges in the internationalization of business schools especially in the global South (Alcadipani and Faria, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation